ASSESSMENT OF TAX DEBT IN UZBEKISTAN AND THE PROCEDURE FOR COLLECTION - Ashurova Oltin Yuldashevna; Ziyodullayeva Laziza; Ulmasov Davlat (Ecominds Press, 2025)
This article covers the content of the tax debt assessment process, the stages and mechanisms of their collection. Also, proposals are developed to reduce tax debts, increase the efficiency of collection, and ensure the stability of state budget revenues. The study covers the regulatory framework, international experience, and existing problems in the practice of Uzbekistan.
Keywords: Tax debt; tax burden; tax debt assessment; tax rate